Organizational psychologist and facilitator of learning: its main role - Solf Zárate, Arturo (2014)
This article emphasizes that the main role of organizational psychologists should be, facilitate and promote the learning of workers, groups, and the company as a whole. Give this address would allow a better professional contribution, and at the same time would be a challenge to increase their level of expertise.The text focuses only on the level of individual learning. In first part included a theoretical framework, to then present some actions can or could perform the psychologist to facilitate the learning of the workers. Finally a questionnaire is included in the annex to perform a brief diagnosis of the potential offered by an organization to stimulate continuous learning of staff.